Childhood antibiotics as a risk factor for Crohn's disease: The ENIGMA International Cohort Study. Issue 6 (1st June 2022) - Mak, Joyce W Y; Yang, Sun; Stanley, Annalise; Lin, Xiaoqing; Morrison, Mark; Ching, Jessica Y L; Niu, Junkun; Wilson‐O'Brien, Amy L; Feng, Rui; Tang, Whitney; Hamilton, Amy L; Or, Leo; et al.
Abstract: Background and Aim: Environmental factors play a key role in development of Crohn's disease (CD), thought to be mediated by changes in the gut microbiota. We aimed to delineate the potential contribution of antibiotic exposure to subsequent development of CD, across diverse geographical populations. Methods: This case–control study in Australia and three cities in China (Hong Kong, Guangzhou, and Kunming) included four groups: patients with CD, at‐risk individuals including non‐affected first‐degree relatives (FDRs) and household members of CD patients (HM), and unrelated healthy controls (HCs). Environmental risk factors, including childhood antibiotic use and 13 other categories, were assessed using a self‐developed questionnaire. Logistic regression and conditional logistic regression were used to determine environmental factors associated with CD development. Results: From 2017 to 2019, a total of 254 patients with CD (mean age: 37.98 ± 13.76 years; 58.3% male), 73 FDR (mean age: 49.35 ± 13.28 years; 46.6% male), 122 HMs (including FDR) (mean age: 45.50 ± 13.25 years; 47.5% male), and 78 HC (mean age: 45.57 ± 11.24; 47.4% male) were included. Comparing CD patients with their FDR and HMs, antibiotic use before 18 years old was a risk factor for CD development (adjusted odds ratio [OR] 3.46, 95% confidence interval [CI] 1.38–8.69; P  = 0.008). There were no significant differences in other childhood environmental risk factors between CD and their FDR or HMs. Subgroup analysis showed that antibiotic use <18 years old was a risk factor for CD development in the Chinese (adjusted OR 4.80, 95% CI 1.62–12.24; P  = 0.005) but not in Australian populations (OR 1.80, 95% CI 0.33–9.95; P  = 0.498). Conclusion: Use of antibiotics <18 years was a risk factor for CD development. Attention should be paid to identifying modifiable environmental risk factors in early childhood, especially in at‐risk families. Abstract : Environmental factors play a key role in development of Crohn's disease (CD). Comparing CD patients with their first‐degree relatives and household members, antibiotic use before 18 years old was a risk factor for CD development (adjusted odds ratio 3.46, 95% confidence interval 1.38–8.69). Attention should be paid to identifying modifiable environmental risk factors in early childhood, especially in at‐risk families.